Improved synthesis of phytanyl α-D-cellobiosyldiphosphate as substrate for α-D-mannosyltransferase - Barrios, Pablo Daniel (2011)
Polyisoprenyl-pyrophosphate-linked cellobiose is the natural acceptor of the α-1,3- mannosyltransferase AceA from Acetobacter xylinum, which transfers mannose from GDPmannose during the assembly of the heptasaccharide repeat unit of the exopolysaccharide acetan. Phytanyl α-D-cellobiosyldiphosphate 4 has been previously synthesized as an analogue acceptor by condensation of hepta-O-acetyl-α-D-cellobiosylphosphate 1 with phytanylphosphate 2, but the procedure was briefly described. We report here a modified detailed synthesis of 4. The complete NMR characterization of 4 is provided and also a selection of NMR signals of all the intermediate compounds which facilitate monitoring the synthesis.